The Role of Neuro Linguistic Programming (NLP) in Modeling Human Excellence and Mental Skills to Accelerate Learning: Uncovering the exact thought process underlying successful results - Bouallaga, Meriem (University of Eloued جامعة الوادي, 2016)
This paper aims basically at sheding the light up on the the distinctive role of Neuro Linguistic Programming (NLP) in modeling human excellence and mental skills in order to accelerate the learning process for our learners, and at highliting or uncovering the exact thought process underlying successful results of those who are considered to be super-fast learners. In fact, there is a missing piece in our educational system. We do not teach students how to learn in the classroom. Specifically, we do not teach them what to do inside their mind. The missing piece is that we are not considering the students‘ mental strategies. We just assume they will learn if we teach in enough different ways. There are lots of great teachers and wonderful teaching methods out there to present the information and there are many ways to evaluate the students to see how much they have learned. But what about the part in between when the student is thinking, processing, and memorizing the information. Some students pick up effective ‗mental strategies‘ for learning and memorizing and others don‘t. Learning in school is in fact a mental skill that needs to be taught to those students who don‘t. The thought process a person goes through to get a particular result was a foggy factor, until NLP came along and gave us a precise way to uncover a person‘s thinking process. Thus our goal is to simulate a precise model of what these persons do and what they think. And then building a complete model to teach it to someone else, teach the most effective mental or thinking strategies in order to accelerate the learning process.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Neuro Linguistic programming, mental skills, modeling human excellence, accelerated learning, thought process